Perbedaan Skor OSDI Pre dan Post Senam "PERMATA-KU" pada Computer Vision Syndrome - Uyun, Fuadah; Rahmi, Fifin Luthfia; Saubig, Arnila Novitasari; Julianti, Hari Peni (Medica Hospitalia : Journal of Clinical Medicine, 2021)
ABSTRACT DIFFERENCE OF OSDI SCORE BEFORE AND AFTER ‘SENAM PERMATA-KU’ IN COMPUTER VISION SYNDROME Background: Computer Vision Syndrome (CVS) is a group of symptoms that affects the eye and vision due to prolonged use of computer, cellphone, tablet, and e-reader. Dry eye is one of the symptoms that appear in CVS. In this study we did ‘senam PERMATA-KU’ (Pelihara Mata–Kendorkan Bahu) as additional exercise to reduce dry eye in CVS. Aim: Observe there is any improvement of OSDI (Ocular Surface Disease Index) score before and after doing “senam PERMATA-KU” in CVS. Methods: This was a Pre-Post with Control Design quasi experimental study. The subjects were students of Faculty of Medicine of Diponegoro University who had CVS and met the inclusion and exclusion criteria that were divided randomly into control group and experimental group. The experimental group were given an education about using computer ergonomically and ‘senam PERMATA-KU’ for 14 days. The control group were given an education about using computer ergonomically. OSDI score were measured before and after intervention was given using Ocular Surface Disease Index questionnaire. Result: The subjects were 32 students with 16 students in the experimental group and 16 students in the control group. One student in the control group and one student in the experimental group dropped out because they could not complete the procedure so that only 30 subjects were analyzed. OSDI score after intervention in experimental group was decreased significantly (p<0.05). OSDI score after intervention in experimental group was better compared to control group (p<0.05). OSDI score improvement in experimental group was higher compared to control group but statistically is not significant (p=0.595). Conclusion: ‘senam PERMATA-KU’ that was done for 14 days can improve OSDI score in Computer Vision Syndrome. Keywords: Computer Vision Syndrome (CVS), Ocular Surface Disease Index (OSDI), dry eye, ‘senam PERMATA-KU’